Do the male with type D personality have more mental symptoms? Evidence from coping tendency of Chinese college students. (July 2021) - Wang, Shengnan; Zhao, Licai; Jia, Xuji; Yin, Xunbao; Tan, Xia; Lyu, Juncheng; Sun, Hongwei
Abstract: The objective of the current study was to explore the possible mechanism in a non-clinical population. A self-reported survey was conducted among 2016 Chinese college students through questionnaires assessing Type D, coping tendency and mental symptoms. As a normal personality subtype, the incidence of Type D in the sample is higher. Compared with the scores of type D − group, the type D + group's score of positive coping tendency was lower and that of mental symptoms was higher. Type D can exert an effect on mental health directly, and indirectly through coping tendency. Moreover, there was a gender difference in the mediating path. The mediation effect of coping tendency is more prominent in men, and the male have more mental symptoms than the female while they have the same Type D score. Highlights: Of the participants in the present study, 33.23% were classified as Type D. There were differences between Type D and non-Type D in all comparison items. Type D could affect mental health directly and indirectly through coping tendency. The mediation impact of coping tendency was stronger in males.